UJI EFEKTIFITAS KINERJA INSTALASI PENGOLAHAN LENGKAP AIR GAMBUT DALAM MENURUNKAN KADAR BESI (Fe) DAN WARNA DI PARIT SUNGAI RAYA DALAM - Sismiarty, Nuniek; Budiastutik, Indah; Asmadi, Asmadi (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Water is essential to human health and it effect all facets of life. It is pertained to a group of residents in Parit Sungai Raya Dalam neighborhood who use peat water as an alternative of clean water. Peat water contains both iron (Fe) and high colour intensity so that it is not suitable for daily activities. It is recognized that peat water may cause some negative effect for health. Based on the background before hand, the purpose of this research was to find out the effectiveness of the peat water treatment installation in Parit Sungai Raya Dalam in reducing the iron concentration (Fe) and its colour. There were some processes applied in this procedure namely, neutralization process, coagulation, sedimentation, filtration and ultrafiltration. Â In line with the purpose, this research was conducted by employing a pre experimental design with one group pretest-posttest design with control. The data gathered were analyzed by using statistical T-test. Based on the laboratory test results,it was found that there was a decreasing iron value before treatment as in 5,60 mg/l to 0,13 mg/l when the water concentrated at low tide with its effectiveness decline 97,6%. A decreasing iron value was 6,29 mg/l to 0,23 mg/l when the water concentrate at high tide. Its effectiveness decline was 96,1%. The colour before treatment at low tide as was 1202,31 PtCO to 21,14 PtCO with 98,1% effectiveness decline, and the colour before treatment at high tide was 1338,38 PtCO to 22,25 PtCO with 98,2% effectiveness decline. The findings showed that the result of the peat water treatment installation can produce a feasible clean water based on the quality standars of the regulation of the health Minister of the Republic of Indonesia No.416/Menkes/Per/IX/1990 about requirements and Monitoring of Water Quality where the quality standards Â for iron concentration (Fe) should not exceed 0,2 mg/l and the maximum colour is 50 PtCO. As a result,it is recommended that the society can use peat water with water purification material (PAC) and alum water treatment for feasible clean water.Keywords : Peat water, Filtration,Iron (Fe), Colour Intensity and Ultrafiltration.